Correlative Nano-Computed Tomography and Focused Ion-Beam Sectioning: A Case Study on a Co-Base Superalloy Oxide Scale - Lenz, Malte; Wirth, Janis; Englisch, Silvan; Rosiwal, Jan; Buchinger, Nadine; Weiser, Martin; Virtanen, Sannakaisa; Apeleo Zubiri, Benjamin; Spiecker, Erdmann (Advanced Engineering Materials, 2019)
Herein, the capabilities of a correlative tomography approach combining laboratory nano X-ray computed tomography, focused ion-beam sectioning, and energy-dispersive X-ray spectroscopy are utilized for the characterization of multilayered oxide scales of Co-base superalloys regarding their 3D morphology and chemical composition. The combination of complementary 3D imaging techniques allows for a precise and reliable segmentation of the pore space, oxide precipitates, and different phases of the initial material. Such information is instrumental to a microscopic understanding of oxidation in this new class of superalloys and key to improvement of oxidation resistance in the next-generation high-temperature materials.
CRIS-Team Scopus Importer:2019-11-19
Keywords: cobalt-base superalloys; electron microscopy; focused ion beam/scanning electron microscopy tomography; nano-computed tomography; oxidation